Assessing and predicting the changes for inorganic mercury and methylmercury concentrations in surface waters of a tidal estuary (Adour Estuary, SW France). (January 2023) - Stoichev, Teodor; de Chanvalon, Aubin Thibaut; Veloso, Sandrine; Deborde, Jonathan; Tessier, Emmanuel; Lanceleur, Laurent; Amouroux, David
Abstract: Total and dissolved concentrations of inorganic mercury (IHg) and methylmercury (MeHg) in water (Adour Estuary) were determined during three sampling campaigns and related to biogeochemical variables (nutrients, organic matter). Factors (sampling time, sample type) were included in analysis of covariance with effect separation. The urban estuary suffered historically from anthropogenic sources, however, decreased emissions have reduced Hg concentrations. Total IHg (0.51–3.42 ng L −1 ) and MeHg (25–81 pg L −1 ) concentrations are additively described by suspended particulate matter and particulate organic carbon. Higher total concentrations, carried by organic-rich particles, were found near specific discharge points (0.79–8.02 ng L −1 and 34–235 pg L −1 for IHg and MeHg, respectively). The associated high dissolved MeHg concentrations could not be explained only by biogeochemical variables. Better efficiency of the models is found for total than for dissolved concentrations. Models should be checked with other contaminants or with estuaries, suffering from downstream contamination. Graphical abstract: Unlabelled Image Highlights: Hg species studied in water of estuary with upstream and downstream input 10-Fold decrease of Hg concentrations in 20 years due to lower Hg emission ANCOVA additive models evaluated input of Hg species via organic-rich particles Total Hg species in water additively depicted by particulate organic carbon and SPM Dissolved methylmercury and, especially inorganic Hg sorbed on suspended particles